MR neurography in Parsonage-Turner syndrome - Upadhyaya, Vaishali; Upadhyaya, Divya Narain; Bansal, Richa; Pandey, Tarun; Pandey, Ashok Kumar (Indian Journal of Radiology and Imaging, 2019)
Background and Aims: Parsonage Turner Syndrome is a well known clinical entity. Several excellent articles have succinctly described Magnetic Resonance Imaging (MRI) findings in PTS. However, these articles have inferred neural involvement in PTS based on the patterns of denervation of muscles in the shoulder region. The aim of this study is to directly visualize the distribution and extent of abnormality in MR Neurography (MRN) of the brachial plexus in known cases of brachial plexus neuritis or Parsonage-Turner Syndrome (PTS). Methods: 15 patients who were diagnosed with PTS based on clinical and electrophysiological findings participated in the study. MRN of the brachial plexus was done in a 1.5T system using a combination of T1W (T1-weighted), T2W (T2-weighted) fat-saturated, STIR (Short Tau Inversion Recovery), 3D STIR SPACE (Sampling Perfection with Application Optimized Contrasts) and 3D T2W SPACE sequences. Findings were recorded and assessed. Results: The age range of our patients was 7-65 years (mean 37.87 years). Most of the patients had unilateral symptoms. All patients had weakness in shoulder abduction. Other common associated complaints included pain in the shoulder/neck/arm and preceding fever. MRN revealed the percentage of involvement of roots, trunks, cords and terminal branches was 53.3%, 46.7%, 40% and 13.3% respectively. Evidence of muscle denervation in the form of edema, fatty infiltration and atrophy was noted in 8 (53.3%) patients. Conclusion: Most of the patients in this study had unilateral involvement on MRN. The roots were the commonest site of involvement followed by the trunks, cords and terminal branches. C5 was the most commonly involved root.
Keywords: Brachial plexus; MR Neurography; magnetic resonance imaging; neuritis; parsonage-turner syndrome